PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT. BANK NEGARA INDONESIA (Persero) Tbk. - Prima Anggraeni Hartutik; Abdul Wahid Mahsuni; M. Cholid Mawardi (Universitas Islam Malang, 2020)
ABSTRACTThe multidimensional crisis, especially the economic crisis that hit Indonesia in mid-1997, gave rise to the concept of Good Corporate Governance. As a result of this crisis occurred when many companies fell because they were unable to maintain their business continuity. In this globalization era, a company must have the ability to carry out its business activities in a clean, healthy and ethical manner. Therefore, in realizing the concept of Good Corporate Governance, it is necessary to implement an effective internal system and business ethics.The results of this study indicate that the principles of Good Corporate Governance have been applied well to PT. BNI (Persero), Tbk East Java Distribution Malang Branch Office. The problems that are placed by the company are: “How is the implementation of Good Corporate Governance for employees”. The problem steps taken by the company are to implement effective Good Corporate Governance which includes the main principles of Good Corporate Governance, including: transparency, responsibility, independence, equality and accountability. In addition, the company also applies business ethics in its corporate environment.Based on the discussion of these problems, the suggestions that can be put forward, among others, should PT. BNI (Persero), Tbk Distribution East Java Malang Branch Office takes concrete steps in implementing a Good Corporate Governance system for employee management, and always socializes the meaning of Good Corporate Governance at every opportunity. Keywords : Good Corporate Governance, Internal Control System, Business Ethics